A Comparative Study and Enlightenment on the Current Status of Pediatric Hospice Care Research in China and Abroad - Quhai SHI; Fangyuan LI; Yunan YI; Ying ZHANG (Yixue yu zhexue, 2025)
In response to the lack of pediatric hospice services and the urgent need for systematic construction in China, the study firstly combed the development and research achievements of pediatric hospice care in China and abroad, and then focused on the current situation of research and service in China. Through comparative analysis, several challenges are identified, including structural imbalances in resource allocation and service accessibility, significant data gaps, and narrow or disconnected research directions. Therefore, the study suggests building a comprehensive pediatric hospice service system in China from a holistic perspective. This involves leveraging the specialized operations of social organizations and social work institutions, fostering close collaboration with multidisciplinary professionals, diversifying service providers, developing localized care models, and promoting the practical implementation of services.